Glutathione Peroxidase 3 Serum Levels and GPX3 Gene Polymorphisms in Subjects with Metabolic Syndrome - Baez-Duarte, Blanca G.; Mendoza-Carrera, Francisco; García-Zapién, Alejandra; Flores-Martínez, Silvia E.; Sánchez-Corona, José; Zamora-Ginez, Irma; Torres-Rasgado, Enrique; León-Chávez, Bertha A.; Pérez-Fuentes, Ricardo (Archives of medical research, 2014)
Glutathione peroxidase 3 (GPx3) plays a main role in removing hydro- and lipoperoxides from the body. Changes in concentration and several single-nucleotide polymorphisms (SNP) at the GPX3 gene have been associated with vascular diseases, but the relationship of GPx3 with metabolic syndrome (MetS) remains unexplored. We undertook this study to determine the association of GPx3 serum levels and several GPX3 SNPs with the presence of MetS in Mexican subjects. Clinical, biochemical, and anthropometric evaluation were conducted in 426 subjects assigned to three groups: control (n = 42); risk group (RG, n = 200), and MetS group (n = 184). Insulin sensitivity (IS) and cardiovascular risk were determined by the QUICKI and TG/HDL-C index, respectively. Serum GPx3 was determined by enzyme immunoassay and polymorphisms within GPX3 gene were identified by nucleotide sequencing. MetS group showed low IS and increased cardiovascular risk with respect to controls as well as higher GPx3 serum levels (172.9 ± 32.2 vs. 145.6 ± 24.8 ng/dL; p <0.05). Only three of the ten GPX3 SNPs screened were polymorphic with two haplotypes observed (CCT and TTA–rs8177404, rs8177406, and rs8177409), indicating tight linkage disequilibrium in this genetic region. No differences for either genotype or allele frequencies among groups were observed, but rs8177409 (allele T) was associated with cardiovascular risk (odds ratio [OR], 4.5; p = 0.0125). This study shows that serum levels of GPx3 are increased in subjects with MetS and that rs8177409 SNP was associated with cardiovascular risk in a Mexican population.